Racialist Interpretation of "Roma Crime" by Cesare Lombroso - Kubiček, Andrej (Zbornik Instituta za kriminološka i sociološka istraživanja, 2022)
Prejudices about Roma and their ancestors as delinquents are still present in various genres of racist narratives, from everyday speech, through media reports, to political performances. Reading several works of the founder of criminology, Cesare Lombroso, reveals that an elaborate antigypsyist discourse was also present in scientific literature in the past. The analysis of this specific form of racism shows a wider ideological framework in which the fantasies about the Roma were shaped – as a dark reflection of the progress of the 19th century and the rise of the bourgeois class. The comparison of Lombroso's view of "Jewish" and "Gypsy" crime is of particular value, since it indicates the different genesis of the stigmas of these ethnic communities. An important segment of the work includes the analysis of the sources used by the Italian criminologist. The persistence of the content reproduced by this author points to the long-term influence of the social processes that shape them, regardless of the sources of ideological legitimization. The positivist phase of biological justification of such beliefs is only one segment of the history of Roma stigmatization.